Fluorometric detection of a chemical warfare agent mimic (DCP) using a simple hydroxybenzothiazole–diaminomaleonitrile based chemodosimeter. (2nd December 2022) - Das, Manas Kumar; Mishra, Tanushree; Guria, Subhajit; Das, Debojyoti; Sadhukhan, Juheli; Sarker, Sushmita; Dutta, Koushik; Adhikary, Arghya; Chattopadhyay, Dipankar; Adhikari, Susanta Sekhar
Abstract : Diethyl chlorophosphate (DCP) has a similar reactivity to sarin, which is widely known as a nerve agent that is often used in terrorist attacks. Abstract : Diethyl chlorophosphate (DCP) has similar reactivity to sarin, which is widely known as a nerve agent that is often used in terrorist attacks. As DCP lacks high toxicity, it can be used as a model compound for sarin detection. Besides their use as chemical warfare agents (CWAs), organophosphorus compounds (OPs) also have greater implications for human health. To maintain the balance in global security the first and most in demand work is to establish efficient detection methods for monitoring CWAs. The work presented here reports a benzothiazole-based fluorescent chemodosimeter (BZ-DAM) for the fluorogenic detection of DCP via the ESIPT assisted ICT mechanism. The benzothiazole unit serves as a fluorophore, whereas the phenolic and imine groups act as a recognition unit for DCP. In this mechanistic path, the phenol group in BZ-DAM is phosphoesterified by DCP, which leads to a significant fluorescence change and assists the hydrolysis of the aldemine of BZ-DAM. The detection limit was found to be 0.43 μM by the fluorescence method. BZ-DAM is also stable in biological mediums and a physiological pH range and can be successfully used to detect intracellular DCP in living cells. Scanning electron microscopy (SEM) studies of a polycaprolactone (PCL)-BZ-DAM composite also revealed partial deformation of the surface of the nanomaterials upon the adsorption of DCP, indicating a DCP-mediated chemical transformation.